Effects of Dy2O3 doping on physical and mechanical characteristics of B2O3-TeO2-BaO glass - Saba Hathot; Balqees Al dabbagh; Haydar Aboud (Engineering and Technology Journal)
A new oxide glass host of the form (50-x) B2O3-25TeO2-25BaO-xDy2O3 (where x was varied from 0 to 1.25 mol%) was prepared using the conventional melt-cast quenching method. The study investigated how the glasses' structural, physical, and elastic properties were affected by varying amounts of Dy2O3. The XRD patterns of the samples indicated that they possessed an amorphous nature. FTIR spectrum displayed the vibration mode of trigonal and bipyramidal units like TeO3, TeO4, BO4, and BO3 together with Te-O-Te and Te-O linkages, indicating bridging oxygen (BO). The observed increase in the density (from 4.535 - 4.772 gm.cm-3) was ascribed to the network structure contraction. The improvement in the elastic moduli of the glasses (obtained from the measured shear and longitudinal acoustic velocity) was mainly due to Dy2O3 doping with higher molecular weight. Consequently, it increased the glass rigidity by forming more BO in the glass network, altering the physical and structural characteristics. The obtained rise in the Debye temperature (from 334.0107–351.383 K) and softening temperature (from 399.6075-451848 K) was due to BO-mediated changes in CN. (coordination number) of the glass network. It was shown that the mechanical and structural characteristics of the proposed glass host can be tailored by tuning the Dy2O3 contents. These glasses may be useful for making high-strength optical fibers.